2019
DOI: 10.1016/j.healthplace.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of simulation modeling in built environment and physical activity research: Current status, gaps, and future directions for improving translation

Abstract: Existing reviews have suggested that simulation studies of physical activity and environments are an emerging area, but none have explored findings in this area systematically. We used a scoping review framework to assess the use of simulation modeling to inform decision-making about built environment influences on physical activity. A systematic literature search was conducted in multiple databases in January 2018. Sixteen articles met the inclusion criteria. The studies evaluated interventions and features t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
0
6
0
1
Order By: Relevance
“…As with any review, we may have missed relevant articles in our search. However, we built a comprehensive and systematic search along with a trained information specialist, and used terms similar to previously published reviews of simulation modeling [ 130 ] and SSB warning labels [ 11 ]. Our inclusion/exclusion criteria enabled us to include a range of studies, yielding a comprehensive commentary on the state of the science and allowing us to identify important considerations for future SSB policy simulation modeling.…”
Section: Discussionmentioning
confidence: 99%
“…As with any review, we may have missed relevant articles in our search. However, we built a comprehensive and systematic search along with a trained information specialist, and used terms similar to previously published reviews of simulation modeling [ 130 ] and SSB warning labels [ 11 ]. Our inclusion/exclusion criteria enabled us to include a range of studies, yielding a comprehensive commentary on the state of the science and allowing us to identify important considerations for future SSB policy simulation modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Large scale ABMs have been developed using census data and/or Geographic Information Systems (GIS) to represent geographical areas, mainly for infectious disease modeling (Duan et al, 2015), to enable the assessment of the impact of interventions changing aspects of the physical environment. Frerichs et al (2019) undertook a scoping review of simulation modeling of the built environment and physical activity, and found that of 16 studies, only 7 were real-world applications (5 US, 1 France, 1 Colombia). Whilst the incorporation of the physical environment within ABMs of public health interventions has received relatively little attention, this is not due to data limitations.…”
Section: The Physical Environmentmentioning
confidence: 99%
“…Most of the included literature syntheses for the Theorizing category reviewed applications of system dynamics modelling (SDM) or agent-based modelling (ABM) in public health, chronic disease and obesity [48][49][50][51][52]. Two studies were focused on PA in terms of assessing the use of simulation modelling to inform decision-making about built environment influences on PA [53], and examining the use of systems-based simulation studies to evaluate the health-related consequences of active transport [54].…”
Section: Theorizingmentioning
confidence: 99%